Edukacyjne aspekty działalności agroturystycznej w Polsce - Wartecka-Ważyńska, Agnieszka (Kultura-Społeczeństwo-Edukacja, 2018)
The paper addresses the problems of education, including environmental and cultural education, of children and young people offered by agritourism farms. The study also indicates the need for school education and extracurricular education of families involved in agritourism. Professional employees in agritourism represent precious human capital for rural areas and guarantee high quality of services, e.g. educational services for tourists, including children and young people. The particular focus was on education in the field of ecology and rural cultural heritage. Institutions in one way or another involved in education in agritourism were also discussed. The paper was written based on literature and results of empirical studies.